2020
DOI: 10.1096/fj.202000897r
|View full text |Cite
|
Sign up to set email alerts
|

Platelet inhibition by ticagrelor is protective against diabetic nephropathy in mice

Abstract: Diabetic nephropathy (DN) is a major complication of diabetes and is associated with high risk for cardiovascular mortality, which is partially related to elevated platelet activity. Platelets are also active players in inflammation and fibrosis. In this study, we examine the effect of ticagrelor‐induced platelet inhibition on the development of DN. DN was induced by unilateral nephrectomy followed by streptozotocin injections for 5 days. Mice received ticagrelor (300 mg/kg) or vehicle every other day, for 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“… 65 Subsequent mechanistic studies in a mouse model for diabetic nephropathy demonstrated that the platelet P2Y12 inhibitor ticagrelor could counteract disease progression by lowering albuminuria, mesangial matrix expansion, macrophage infiltration, and fibrosis. 66 Future studies with selective platelet inhibitors such as GLP-1 analogues 67 could well augment our therapeutic options in progressive ischemia-associated diseases of the kidney.…”
Section: Theme 1: the “Coagulome” As A Critical Driver Of Cardiovascu...mentioning
confidence: 99%
“… 65 Subsequent mechanistic studies in a mouse model for diabetic nephropathy demonstrated that the platelet P2Y12 inhibitor ticagrelor could counteract disease progression by lowering albuminuria, mesangial matrix expansion, macrophage infiltration, and fibrosis. 66 Future studies with selective platelet inhibitors such as GLP-1 analogues 67 could well augment our therapeutic options in progressive ischemia-associated diseases of the kidney.…”
Section: Theme 1: the “Coagulome” As A Critical Driver Of Cardiovascu...mentioning
confidence: 99%
“…It is therefore essential to understand the changes of coagulation factors in DKD with respect to its critical roles involving the activation of the complement and the consequent inflammation-induced fibrosis in DKD. The correction of abnormality of the coagulation factors is beneficial for patients with DKD as it not only prevents thrombosis but also kidney failure (75,76). The following sections will provide a summary of the dysregulations of critical factors in the coagulation system in DKD and their involvement in inflammation, along with their relevance to the progression of DKD.…”
Section: Signaling Pathways Contribute To Inflammatory Fibrosis Evolv...mentioning
confidence: 99%
“…In addition to its platelet-inhibition effect, ticagrelor has been shown to be effective in the treatment of acute coronary syndromes (ACS) and kidney disease. The effect of ticagrelor in DKD was examined by Uil et al [ 179 ]. They studied the effect of platelet inhibition by ticagrelor in an STZ-induced T1DM mouse model.…”
Section: Therapeutic Perspectives Of Platelet Inhibitors In Dkdmentioning
confidence: 99%